2012
DOI: 10.1186/1472-6882-12-204
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of rutin against potassium bromate induced nephrotoxicity in rats

Abstract: BackgroundRutin, a polyphenolic flavonoid, was investigated for its protective effects against the KBrO3 induced renal injuries in rat.MethodsGroup I was control (untreated), group II was given saline 0.5 ml/kg bw (0.9% NaCl), group III was administered KBrO3 (20 mg/kg bw) intragastric twice a week for four weeks. Rutin was administered to group VI (50 mg/kg bw) and Group V (70 mg/kg bw) along with KBrO3 (20 mg/kg bw) while group VI was given rutin (70 mg/kg bw) alone twice a week for four weeks. Protective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 57 publications
5
55
0
Order By: Relevance
“…Destruction of the hepatocytes induced by KBrO 3 caused significant ( P < 0.05) rise in AST and ALT in Group III which was supported by the histological alterations that appeared. This agrees with the earlier studies which reported increase in ALT and AST in rats administered with 20, 50, 100, and 200 mg/kg of KBrO 3 (Khan et al, ; Dimkpa et al, ). Conversely, the significant reduction in enzyme activities of rats treated with vitamin C suggests its capability to improve the deleterious effects of KBrO 3 .…”
Section: Discussionsupporting
confidence: 93%
“…Destruction of the hepatocytes induced by KBrO 3 caused significant ( P < 0.05) rise in AST and ALT in Group III which was supported by the histological alterations that appeared. This agrees with the earlier studies which reported increase in ALT and AST in rats administered with 20, 50, 100, and 200 mg/kg of KBrO 3 (Khan et al, ; Dimkpa et al, ). Conversely, the significant reduction in enzyme activities of rats treated with vitamin C suggests its capability to improve the deleterious effects of KBrO 3 .…”
Section: Discussionsupporting
confidence: 93%
“…The kinetics of amylin fibril growth can be monitored by the specific binding of fluorescent molecule Thioflavin T (ThT) to amylin aggregates 47,48 . Consistent with the ThT fluorescence results, 10 µM amylin alone formed and accumulated cause metabolic dysfunction, ultimately leading to cell death 52 . Co-incubation with rutin significantly reduced the intensity of amylin fibril fluorescence, more than 50% and 95% fibril formation was inhibited by 100 and 300 µM of rutin, respectively (Fig.…”
Section: Rutin Inhibits Amylin Fibrillizationsupporting
confidence: 75%
“…Hence, GSH/GSSG ratio is an ideal indicator for oxidative stress level 43,44 . It reduces hydrogen peroxides and hydroperoxides by redox and detoxification reactions as well as protects protein thiol groups from oxidation.…”
Section: Regulatory Effect Of Rutin On Gsh and Gssg Levelsmentioning
confidence: 99%
“…Khan et al (2012a) found that treatment with rutin, one of the polyphenols presented in grapevine extracts, restored DNA fragmentation and 8-oxo-dG damage, as well as decreasing the p53 and CYP 2E1 expression induced by carbon tetrachloride (CCl 4 ) in rats. Further, the flavonoid rutin (1) decreased levels of ROS, nitric oxide (NO), glutathione disulfide (GSSG), and malondialdehyde (MDA), (2) lowered activity of inducible nitric oxide synthase (iNOS), (3) attenuated mitochondrial damage, (4) increased glutathione (GSH)/GSSG ratio, (5) enhanced activities of SOD, CAT, and glutathione peroxidase (GPx) (Khan et al, 2012a(Khan et al, , 2012bWang (6) modulated production of proinflammatory cytokines by decreasing tumor necrosis factor (TNF)-α and interleukin (IL)-1β generation (Wang et al, 2012). This study showed the antimutagenic activity of V. labrusca cv.…”
Section: Discussionmentioning
confidence: 99%